Characteristic of the zinc- and nickel-containing iron-oxygen nanophases formed on the steel surface under rotation-corrosion dispergation conditions - Lavrynenko, O.M.; Pavlenko, O.Yu.; Shchukin, Yu.S. (Современные проблемы физического материаловедения, 2015)
The nanosized powders formed on the steel surface contacting with zinc and nickel inorganic water salt solutions under the rotation-corrosion dispergation (RCD) conditions have been studied using an X-ray diffraction method, thermal analytical measurements (TG / DTG, DTA) and scanning electron microscopy. It was shown that the formation of a single mineral phase of a non-stoichiometric spinel ferrite when zinc and nickel nitrate solutions were used as the dispersion medium, but in the presence of chloride-containing salts three mineral phases (spinel ferrite, lepidocrocite, and goethite) were determined in the phase composition of the surface powders. When sulfate solutions were chosen as the dispersion medium the mixed hydroxysulfate layered double hydroxides (LDHs) simultaneously appeared among other components of the powders. Due to exchange of cations Fe(II) and other 3d-metals between the disperse phase and dispersion medium the mixed LDH structures achieved stability against further oxidation and phase transformation. Hence, the presence of mixed LDHs in the phase composition of the powders significantly complicates the obtaining of monomineral phases of spinel ferrites or iron oxides when the RCD method is applied. Нанорозмірні суміші залізокисневих фаз отримані за умов ротаційно-корозійного диспергування на поверхні сталі, яка контактує з водними розчинами неорганічних солей цинку і нікелю. Їх будо досліджено методами рентгено-фазового аналізу, диференційного термічного аналізу (ТГ / ДТГ, ДТА) і сканівної електронної мікроскопії. Показано, що при використанні у якості дисперсійного середовища розчинів нітратів цинку та нікелю у складі порошків утворюється єдина мінеральна фаза нестехіометричної феришпінелі. Водночас у присутності Cl–-вмісних розчинів у складі порошків визначено три мінеральні фази (феришпінель, лепідокрокіт і гетит). При використанні у якості дисперсійного середовища SO₄²⁻ -вмісних розчинів у складі порошків, одночасно з іншими фазами з’являються змішані шаруваті подвійні гідроксиди (ШПГ) железа та цинку або нікеля. Обмін катіонами Fe(II) і 3d-металів між дисперсною фазою та дисперсійним середовищем веде до стабілізації структури ШПГ, що значною мірою ускладнює отримання при їх термічному перетворенні мономінеральних фаз феришпінелей та оксидів железа. Наноразмерные смеси железо-кислородных фаз получены на поверхности стали, контактирующей с водными растворами неорганических солей цинка и никеля, в условиях ротационно-коррозионного диспергирования. Смеси исследованы методами рентгенофазового анализа, дифференциального термического анализа (ТГ / ДТГ, ДТА) и сканирующей электронной микроскопии. Показано, что при использовании в качестве дисперсионной среды растворов нитратов цинка и никеля образуется единственная минеральная фаза нестехиометрической ферришпинели. В то же время в присутствии Cl–-cодержащих растворов в составе порошков определены три минеральные фазы (ферри¬шпинель, лепидокрокит и гетит). При использовании в качестве дисперсионной среды SO₄²⁻ -содержащих растворов в составе порошков одновременно с другими фазами образуются смешанные слоистые двойные гидроксиды (СДГ) железа и цинка или никеля. Обмен катионами Fe(II) и 3d-металлов между дисперсной фазой и дисперсионной средой приводит к стабилизации структуры СДГ, что значительно усложняет получение при их термической трансформации мономинеральных фаз ферришпинелей или оксидов железа.